Vaccines in the Fight Against COVID-19: Mechanisms, Efficacy, and Global Challenges - Dr. V. Basil Hans (Recent Trends in Infectious Diseases, 2025)
The SARS-CoV-2 pandemic has created an unparalleled public health problem, necessitating comprehensive prevention. This page discusses COVID-19's evolution, scientific understanding, and quick vaccine production and implementation. It compares the mechanisms, efficacy, and safety profiles of the four major types of COVID-19 vaccines—namely mRNA, viral vector, protein subunit, and inactivated virus vaccines. Each type is evaluated in terms of how it stimulates the immune response, its effectiveness in preventing infection or severe disease, and its known side effects or safety concerns. In addition, the essay delves into the growing issue of vaccine hesitancy, exploring psychological, social, and cultural factors that influence public attitudes. It also highlights the global inequalities in vaccine distribution and access, with a focus on the challenges faced by low- and middle-income countries. Furthermore, it addresses the emergence of novel SARS-CoV-2 variants and the implications for vaccine effectiveness, necessitating the development and administration of booster doses to sustain immunity. The essay concludes by emphasizing that widespread vaccination is critical to controlling the pandemic, and it underlines the need for sustained investment in infectious disease research, public health infrastructure, and international collaboration to prepare for future global health threats.
Keywords: COVID-19; Sars-CoV-2; effectiveness; mRNA vaccines; public health